A clinical practice guideline for the prevention and treatment of peri-implant diseases - Marín-Jaramillo, Rubiel Antonio; Villegas-Giraldo, Alejandro; Duque-Duque, Andrés; Giraldo-Aristizábal, Astrid; Muñoz-Giraldo, Viviana (Revista Facultad de Odontología Universidad de Antioquia, 2019)
Introduction: the incidence of peri-implant diseases is high, and their optimal management is still debated. The purpose was to explore the levels of available evidence and to suggest evidence-based recommendations for the treatment of peri-implant mucositis and peri-implantitis. Methods: a clinical practice guideline was developed using the Scottish Intercollegiate Guidelines Network (SIGN) criteria. A search strategy was formulated, and a critical review of the following evidence was performed: 1) prevention of peri-implant diseases, 2) treatment of peri-implant mucositis, and 3) treatment of peri-implantitis. Systematic reviews and randomized controlled clinical trials were the primary study types identified in the literature. Current levels of evidence were established and recommendations were provided. Results: a total of 67 articles were included. Regarding the prevention of peri-implant diseases, there is strong evidence for the involvement of patients in a regular maintenance program according to their risk profile. Regarding the treatment of peri-implant mucositis, infection control measures are recommended; controversy exists over the usefulness of antimicrobial agents, and there is evidence against the use of antibiotics. Selection of the peri-implantitis treatment method depends on the severity of the condition and patient-related factors. Resective and regenerative therapies may be used for treatment. The use of systemic antibiotics favors the response of clinical parameters. There is conditional evidence for the use of other adjunctive therapies. Conclusions: the best way to prevent peri-implantitis is to prevent peri-implant mucositis through adherence to supportive periodontal therapy. Treatment of peri-implant diseases depends on local and systemic conditions that affect the success of other treatment options.